Perancangan Sistem Pompa Irigasi Pembangkit Listrik Tenaga Surya (PLTS) Untuk Pertanian Subak Semaagung - Oya Iman Sanjaya; IAD Giriantari; I N Satya Kumara (Program Studi Teknik Elektro UNUD, 2019)
In general the average rice harvest in Indonesia is three times in one year with a rice age of 115-120 days. Subak is an organization owned by farmers in Bali that specifically regulates traditional rice field irrigation systems. Subak Semaagung every year there is a shortage of water on agricultural land. Subak area of approximately 55 hectares consisting of six groups of farmers called